(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study examines the effects of slope segments in gully site at three depths on soil physical, hydraulic and structural stability properties at Amachalla, Awka, Southeastern Nigeria. A total of 36 soil samples were collected from three different slope segments (upper, middle and lower) at three depths (0–15 cm, 15–30 cm, and 30–45 cm) with four replications. These samples were prepared and taken to the laboratory for analysis using standard procedures to determine some soil parameters. The laboratory data were analyzed using Genstat Statistical Package and means were separated by Fisher’s Least Significant Difference (F-LSD) at P<0.05. Results showed that soils in the study area were predominantly loamy sand, with the upper slope containing the highest sand fraction (86.91%) at 15–30 cm depth, while the lower slope recorded the highest silt content (12.27%) at the same depth. The middle slope recorded the highest clay fraction (4.08%) at 0–15 cm. Bulk density values ranged from 1.47 to 1.48 g/cm³, with no significant differences across slopes. Total porosity decreased with depth, ranging from 18.16 to 44.65%. Moisture content was highest (24.55%) in lower slopes at 30–45 cm. Saturated hydraulic conductivity varied from 10.49 to 13.54 cm/hr. Aggregate stability was highest (34.77%) at the lower slope (0–15 cm). Erosion ratio was highest at 263.14 in lower slopes. Based on the findings, emphasis should be placed on slope-specific soil conservation strategies to mitigate erosion risks.